First record of Pentapharsodinium (Peridiniales, Dinophyceae) in the China Sea, with description of Pentapharsodinium dalei var. aciculiferum. Issue 4 (30th June 2013) - Gu, Haifeng; Luo, Zhaohe; Zeng, Ni; Lan, Binbin; Lan, Dongzhao
Summary The dinophyte genus Pentapharsodinium shares an identical plate formula with that of Ensiculifera, but lacks a spine on the first cingulum plate and a median sulcal plate (Sm). Herein we established eight strains by incubating single cysts of Pentapharsodinium dalei from the Chukchi Sea, Yellow Sea, and South China Sea. The six strains from the Chukchi Sea and Yellow Sea fit the description of P. dalei, and they share identical internal transcribed spacer region (ITS1, ITS2 and 5.8S rDNA) sequences. The two other strains (G96 and PDFC01) from the South China Sea are morphologically similar to P. dalei, but they possess a spine on the anterior sulcal plate and an additional Sm plate. These two strains were described as P. dalei var. aciculiferum. They share identical ITS sequences and differ from P. dalei strains PDCH01 (Yellow Sea) and SZN19 (Norway origin) at 20 and 26 positions (96.40% and 95.32% similarity) respectively. Maximum‐likelihood and Bayesian inference resolved a well supported clade consisting of P. dalei and P. dalei var. aciculiferum. Our results reveal that cysts of P. dalei might comprise several morphologically, genetically, and ecologically different varieties.